2014
DOI: 10.1177/0141076814531750
|View full text |Cite
|
Sign up to set email alerts
|

Health information systems in Africa: descriptive analysis of data sources, information products and health statistics

Abstract: Objective: To identify key data sources of health information and describe their availability in countries of the World Health Organization (WHO) African Region. Methods: An analytical review on the availability and quality of health information data sources in countries; from experience, observations, literature and contributions from countries. Setting: Forty-six Member States of the WHO African Region. Participants: No participants. Main outcome measures: The state of data sources, including censuses, surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 3 publications
0
52
0
2
Order By: Relevance
“…173,180 Tools and indicators are fragmented by disease and funding source, with inadequate harmonisation and few national plans for coordination and data use. 180,181 For example, 26 different bilateral, multilateral, governmental, and non-govern mental Panel 10: From measurement to action* Measurement alone will not ensure health system quality. Actionable information must reach agents capable and empowered to use it to effect change in the health system.…”
Section: The Lancet Global Health Commissionmentioning
confidence: 99%
See 1 more Smart Citation
“…173,180 Tools and indicators are fragmented by disease and funding source, with inadequate harmonisation and few national plans for coordination and data use. 180,181 For example, 26 different bilateral, multilateral, governmental, and non-govern mental Panel 10: From measurement to action* Measurement alone will not ensure health system quality. Actionable information must reach agents capable and empowered to use it to effect change in the health system.…”
Section: The Lancet Global Health Commissionmentioning
confidence: 99%
“…148 Barriers to robust implementation and use of electronic health records and DHIS include restricted ownership by end users, scarce training on data skills, lack of motivation and engagement by overburdened health workers, large numbers of indicators required, and inadequate functionality of electronic platforms. 181,190 As a result, data quality in routine health information systems is poor, with vertical programme assessments often identifying high prevalence of missing or inaccurate data. 181,191 New evidence from Kenya, Nigeria, and Mexico suggests that such deficiencies in data quality also pertain to indicators of health system quality (appendix 2).…”
Section: Data Qualitymentioning
confidence: 99%
“…Kerangka HMN bertujuan untuk mengembangkan dan memperkuat sistem informasi kesehatan negara serta membantu dalam penerapan monitoring dan evaluasi yang berkelanjutan (WHO, 2008). Selain itu, kerangka tersebut membantu mengidentifikasi kesenjangan dan isu penting yang dapat dilihat dari sudut pandang stakeholders yang terlibat dalam sistem informasi kesehatan (Mbondji et al, 2014).…”
unclassified
“…Challenges of IDSR in SSA This review indicates that in most countries, data generated through the routine HMIS, which is the key source of IDSR, are rarely assessed for their quality, analysed and used to support decision-making [29]. Several studies in SSA have revealed weaknesses in case identi cation and recording at the primary healthcare facilities [14,24,37,57,72,82].…”
Section: Discussionmentioning
confidence: 99%